2005
DOI: 10.1117/12.603325
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical 3D structural matching in aerospace photographs and indoor scenes

Abstract: The investigation presented in this article continues our long-term efforts directed towards the automatic structural matching of aerospace photographs. An efficient target independent hierarchical structural matching tool was described in our previous paper 1 , which, however, was aimed mostly for the analysis of 2D scenes. It applied the same geometric transformation model to the whole area of image, thus it was nice for the space photographs taken from rather high orbits, but it often failed in the cases wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In this way, an attempt is made to discriminate groups of key points that belong to separate objects. Lutsiv et al 2 use texture analysis for similar purposes. After clusterization, the key points (structural elements) can be correlated within separate subregions, and the final solution is made from the number of correlated regions of the images.…”
Section: Introductionmentioning
confidence: 98%
“…In this way, an attempt is made to discriminate groups of key points that belong to separate objects. Lutsiv et al 2 use texture analysis for similar purposes. After clusterization, the key points (structural elements) can be correlated within separate subregions, and the final solution is made from the number of correlated regions of the images.…”
Section: Introductionmentioning
confidence: 98%
“…[5][6][7] Attempts to apply traditional NNs to such problems have led to more limited solutions, 8 while it has not yet been demonstrated that they can be solved with deep-learning networks having automatic extraction of the corresponding invariants. In this connection, the question arises of whether deep-learning networks can be nontrivially generalized.…”
Section: Introductionmentioning
confidence: 99%